Novel approach for anti-collision planning optimization in directional wells - Mohamed, Abdulrahman (International Journal of Engineering and Technology, 2020)
One of the most application of the directional drilling is drilling multiple wells from one location or platform. In drilling multiple wells from one location the major problem that faced is avoiding the collision with the offset wells that drilled near the proposed well in the same region. Therefore, the Potential of Collison between the wells can cause severe catastrophic accidents such as an explosion or oil spill. Several measurements of proximity calculation or methods have been adopted to control the distance between the wells, avoid the Collison, increas-ing the clearance along with smoothing the trajectory, Reducing the drilling time based on the anti-collision rules. A real case study of an offshore directional horizontal well drilled from the platform is studied through the paper. The proposed well is drilled in the neighboring of three Offset wells that should be Planned completely to avoid the Collison with them. The well is planned through an advanced anti-collision method that results in preventing the collision of well with optimized drilling performance through Oriented separation factor (OSF). This factor yields appropriate separation with OSF greater than 5. This yield efficient separation with offset well 1, offset well 2 and offset well 3 greater thant5, In addition to optimized drilling performance of 84% drilling versus 16% sliding that results in the completion of the well in 50 days with positive income that result in 8.55 Return on Investment (ROI).Â Â Â